Muslim Family Communication in Fulfilling the Rights and Obligations of Husband and Wife in A Long Distance Relationship (LDR) - Sumadi, Sumadi; Nabila Wardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Communication between family members is an important factor in maintaining family harmony, especially in the context of long distance relationships (LDR) which require more effort to maintain communication and trust between partners. In a Muslim family, good communication not only maintains relationships but also ensures that the rights and obligations stipulated in Islamic law are properly respected. Marriage is an agreement between a man and a woman to live together as one family, including respecting rights and obligations according to applicable laws and regulations. A long distance relationship describes a couple who are physically apart for certain reasons such as work. Research shows that good communication during a LDR can increase the chances of success in a relationship. In Kertasari Village, several couples who live far apart for work reasons experience difficulties in carrying out the rights and obligations of husband and wife. Previous research has examined strategies for maintaining family harmony in LDR countries, as well as the formation of sakinah families in this context. However, detailed explanations of communication in Muslim families have received little attention. Therefore, studying Muslim family discourse in the communication process to fulfill rights and obligations in LDR is a new discovery in Muslim family research.